MEDIEVAL MUSLIM BURIALS OF A MAN WITH COMBAT INJURIES AT DERBENT WALLS - Gadziev, Murtazali Serazutdinovic; Frizen, Sergej Ur'evic (History, Archeology and Ethnography of the Caucasus, 2020)
In the territory of the Derbent settlement of the I-VI centuries AD, a Muslim necropolis emerged in the Middle Ages; 71 burials were excavated on the site in 1977, 1989, 2012, 2013, 2015-2019. The paper publishes with interpretations a rare representative medieval complex – burial № 24, discovered in the dig XXV (2016). As other Muslim burials of the same cemetery, the one under study was dug in a simple narrow pit (Arab. shiqq / shaqq ‘a trench’) in compliance with all the Muslim funerary norms: the buried laid stretched out on his back, head to the west, the skull turned to the right with the facial bones to the south in the direction of the qibla; no grave goods were revealed. A man of 45-55 years old, of average height and build was buried in the grave. Traces of three simultaneous injuries from saber blows were recorded on the skull, one of which qualifies as fatal. The dating of the burial, as well as of other burials of the necropolis, is guided by the discovery of a tombstone with an epitaph and a date (915 AH / April of 1509 – April of 1510), along with a fragment of another tombstone. The epitaphs of both tombstones mention the title shahid, which was granted postmortem to the buried men. The indicated date provides an opportunity to compare the burials of shahids with military-political events of that time in the East Caucasus, when in 915 AH an army of Ismail I attempted to conquer Shirvan in the name of the struggle between Shiahs and Sunnis, and seized Shemakha, Baku, Shabran, and then sieged Derbent. The burial № 24, in which the man with traces of battle injuries was buried, obviously dates back to the same time period.